POSITIONING MALAYSIA in the INTERNATIONAL ARENA - Mustaffa Mohamed Zain, editor 653183; Norashfah Hanim Yaakop Yahaya Al-Haj, editor 653184; Nurol'ain Mustapha, editor 653185; Zarina Abu Bakar, editor 653159; Mimi Zaleha Abdul Ghani editor 653186 (Shah Alam : University Publication Centre (UPENA), UiTM, 2007)
Positioning Malaysia in the International Arena was the theme for the fifth Perdana Discourse Series. The discourse was an interactive platform where participants had the opportunity to share and discuss issues relating to policies, strategies, and possible models and achievements accomplished during the tenure of Malaysia's previous Prime Ministers. Participants comprised of university students, academicians, senior civil servants and members of various youth associations. The discourse started with a keynote address by Tun Dr Mahathir sharing his thoughts and ideas on the topic. This was preceded by a moderated discussion session chaired by UiTM's Assistant Vice Chancellor, Associate Professor Dr Mustaffa Mohamed Zain. The panel discussants were Dato' Harun Siraj, Professor Azman Awang, Professor Zulaiha Ismail and Mohd Rafa'ei Mohd Tahir. Each presenter took the opportunity to reiterate, list and illustrate several key decisions, and the contributions of the past four leaders on Malaysia's position in the international arena.